Is the National Wages Council Necessary to Singapore's Economic Progress? - PANG, Eng Fong (Institutional Knowledge at Singapore Management University, 1980)
This year, the National Wages Council (NWC), a body comprised of union, employer, and government representatives, will render its 10th recommendation for wage increases in Singapore, thus completing a decade of guided wage increases. Now that the 3-year higher wage readjustment period prescribed by the government is almost over, observers are questioning whether the NWC has any other role, and critics are suggesting that the body might actually be standing in the way of progress. The accepted wisdom in Singapore is that NWC guidelines benefit the country, but some believe that NWC mandates constrain market forces, and thus inhibit rapid adjustment of labor supply to changing patterns of labor demand. NWC's emphasis has changed from pure wage recommendations to regulation and interference with market forces, the assumption seemingly being that market forces cannot be trusted to produce the best results for the Singapore economy. A guided wage policy is no longer in the best interests of Singapore because it does not lend itself to the development of a high technology manufacturing sector and professional/technical personnel that are important to the nation's future.